Analysis of Community Financial Literacy Levels towards Sharia Financial Institutions, Case Study in Menganti Village, Jepara Regency - Pontiningsih, Nely; ansori, miswan (Jurnal Ecoment Global, 2024)
Objective: This research aims to analyze the level of community financial literacy towards sharia financial institutions in Menganti Village, Jepara Regency Design/Methods/Approach: This research uses a quantitative method with a survey approach, where data is collected through questionnaires distributed to the Menganti Village community. Findings: The research results show that the level of sharia financial literacy of the Menganti Village community is in the medium category with an average score of 71.99%. Basic knowledge of sharia finance had the est score with 83.52%, followed by sharia investment dimensions (71.85%), sharia savings and loans (66.67%), and sharia insurance (65.93%). Originality/Value: This research has significant novelty with its specific focus on community financial literacy in rural areas, which until now has received little attention in the academic literature. Most previous research places more emphasis on financial literacy in urban areas or in the context of conventional financial institutions. Practical/Policy implications : the research recommends to stakeholders, including Bank Indonesia, the Financial Services Authority, sharia financial institutions, and educational institutions, to further strengthen and expand sharia financial education in society.